A single-center culture-based study of Helicobacter pylori in Kazakhstan with regional meta-analysis of prevalence and antibiotic resistance - Dauyey, Kaisar; Zhunussova, Gulnur; Kaibullayeva, Jamilya; Bondar, Yevgeniya; Yerzhan, Arailym; Medetbekova, Aliya; Kaisina, Aliya; Khabizhanova, Alma; Seitbekov, Kanat; Yamaoka, Yoshio (Frontiers in Microbiology, 2026)
BackgroundHelicobacter pylori (H. pylori) is a major gastric pathogen and class I carcinogen that causes chronic gastritis, peptic ulcer, and gastric cancer if left untreated. However, evidence on H. pylori prevalence and antimicrobial resistance in Kazakhstan, a country with a high gastric cancer burden, remains scarce. This study presents the first culture-based epidemiological investigation of H. pylori at a single center in Almaty.Materials and methodsWe conducted a cross-sectional study (2024–2025) of 150 dyspeptic patients in Almaty, Kazakhstan. A subset (n = 148) underwent rapid stool antigen (RAS) testing before gastric biopsy collection. Biopsy samples were cultured, and 86 (57.3%) yielded viable H. pylori isolates. Antimicrobial susceptibility testing by the agar dilution method was performed on these 86 isolates. Demographic and clinical data were analyzed, and a regional meta-analysis was conducted using data from recent studies across Central Asia and Russia to estimate pooled prevalence and clarithromycin resistance.ResultsAmong 148 patients tested by RAS, 137 were positive. Resistance rates among 86 isolates were 87.2% to metronidazole, 33.7% to clarithromycin, and 3.5% to amoxicillin; no resistance was detected to minocycline or sitafloxacin. Multidrug resistance (defined as resistance to two or more antibiotics) was observed in 34.8% of isolates. The pooled H. pylori prevalence across Central Asian studies was 70% (95% CI: 59–80%), and pooled clarithromycin resistance was 29% (95% CI: 10–53%).ConclusionThis study provides the first culture-based evidence of H. pylori infection and antimicrobial resistance in Kazakhstan. The high resistance to metronidazole and clarithromycin suggests a likely lower success of standard triple therapy in Almaty. Absence of resistance to minocycline and sitafloxacin supports their use in rescue regimens. These findings highlight the urgent need for national surveillance, updated treatment guidelines, and integration of molecular resistance monitoring to improve evidence-based management of H. pylori in Central Asia.